User interface design for a zoonosis prediction system - Permanasari, A.E. (Taylor's University, 2018)
Zoonosis is any diseases that are transmitted from animal to human. The high-risk impact on zoonosis is increasing since we live in the same environment with some animals. There is important to enhance our attentions to resolve this kind problem. Previously, zoonosis prediction framework has been proposed. This framework was able to predict the number of human incidence of seasonal zoonosis. However, it still needs to transform the framework into a user-friendly user interface. This study examined concerns about the construction of user interface application of zoonosis prediction framework. The results demonstrate decision support system (DSS) architecture. The design covers three DSS components, namely database management subsystem, model base management subsystem, and user interface subsystem. Spreadsheet DSS was applied for the zoonosis prediction application. The model was developed by using the VBA for Excel. In conclusion, the finding determines that the interface can integrate three DSS components in a single DSS interface. Â© School of Engineering, Taylorâs University.